Identifying Markers of Emerging SARS-CoV-2 Variants in Patients With Secondary Immunodeficiency - Markarian, Nathan M.; Galli, Gaël; Patel, Dhanesh; Hemmings, Mark; Nagpal, Priya; Berghuis, Albert M.; Abrahamyan, Levon; Vidal, Silvia M. (Frontiers in Microbiology, 2022)
Since the end of 2019, the world has been challenged by the coronavirus disease 2019 (COVID-19) pandemic. With COVID-19 cases rising globally, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to evolve, resulting in the emergence of variants of interest (VOI) and of concern (VOC). Of the hundreds of millions infected, immunodeficient patients are one of the vulnerable cohorts that are most susceptible to this virus. These individuals include those with preexisting health conditions and/or those undergoing immunosuppressive treatment (secondary immunodeficiency). In these cases, several researchers have reported chronic infections in the presence of anti-COVID-19 treatments that may potentially lead to the evolution of the virus within the host. Such variations occurred in a variety of viral proteins, including key structural ones involved in pathogenesis such as spike proteins. Tracking and comparing such mutations with those arisen in the general population may provide information about functional sites within the SARS-CoV-2 genome. Herein, we review the current literature regarding the specific features of SARS-CoV-2 evolution in immunocompromised patients. We identify recurrent de novo amino acid changes in virus isolates of these patients that can potentially play an important role in SARS-CoV-2 pathogenesis and evolution.